Knowledge Sharing Among Call Center Workers In Cyberjaya - Barcholooei, Simin Khosrowbeygi (2008)
This study investigates the application of knowledge sharing among call centers workers in Cyberjaya, and their associated offices in Kuala Lumpur, and the techniques for improving it. A knowledge sharing model is developed , and its validity is verified by conducting a survey in the call centers.